PEMBERDAYAAN PETANI MELALUI PENDAMPINGAN TEKNOLOGI PERTANIAN BERKELANJUTAN DAN PEMANFAATAN LIMBAH RUMAH TANGGA DI DESA BINJAI SERBANGAN KECAMATAN AIR JOMAN - Fajri, Surya; Syahminar; Safruddin; Agung Gumelar; Pandu Winata; Santy Anggrainy Simbolon (Bersama : Jurnal Pengabdian Kepada Masyarakat, 2025)
Agriculture plays a significant role in economic development and food security in Indonesia, including in Air Joman District, which has great agricultural potential. However, various challenges, such as low productivity and limited access to modern technology, hinder the development of this sector. The community service program by the Faculty of Agriculture at Universitas Asahan aims to enhance farmers' capacities through the implementation of sustainable agricultural technologies. The methods used include counseling and practice-based training, such as utilizing household waste to produce organic fertilizers. Results showed an 85% improvement in farmers' understanding and a 20% average increase in crop productivity. The use of organic fertilizers also reduced production costs by up to IDR 500,000 per planting season, improved soil fertility, and generated additional income for farmers. This program not only provided positive economic and environmental impacts but also contributed to the sustainability of the local ecosystem, making it a replicable model for empowering farmers in other regions.